The Effect of Chrom Element on Oxidation Behaviour of TiAl-based Alloy - Pawawoi (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2009)
Tial-based alloy have long been considered to be suitable candidates for high temperature structural application expecially at below 700oC. Unfortunately, in higher temperature (between 700oC and 900oC), TiAl-based alloy have a poor oxidation resistance. The reason for this is that the alloys generally form rapidly growing titania based surface oxide scales rather than protective alumina layers.Various efforts have been and are being made to overcome these problems. One of alloying elements have been developed is chrom element which hoped could decreased the form of titania and lead to form alumina layers.